Evaluation of knowledge regarding good clinical practice among faculties at a tertiary care teaching hospital - Pandya, Ashna S.; Panchal, Pavan J.; Kataria, Bhaven C.; Parmar, Mitul R. (International Journal of Clinical Trials, 2015)
Background: This study was aimed to assess the knowledge regarding basic aspects of conduct of clinical trial and associated regulatory as well as ethical issues before and after and educational intervention in form of a workshop on Good Clinical Practice (GCP). Methods: One day workshop on “Good Clinical Practice” was planned which included important ethical and regulatory issues regarding clinical research. Various resource persons from industry and academia were chosen to address the workshop. Total 60 participants were enrolled for this one day workshop. Pre-workshop questionnaire of 15 questions were distributed before the actual topic started. Each participant had to fill the questionnaire form and return it within 15 minutes. Again at the end of workshop, post-workshop questionnaire containing the same questions were distributed and the participants were asked to fill the form. Sequence of questions was changed in post workshop questionnaire. Comparison between answers in pre and post workshop questionnaire was done. The primary outcome was knowledge, which was evaluated using the Wilcoxon signed rank test. Results: In Pre workshop, out of 60, total 28 (46.66%) participants had answered all 15 questions, while 30 (50%) participants had skipped to answer one question “Define GCP.” 2 out of 6 (3.33%) participants had not answered 4 and 5 questions out of 15, respectively. Total 45 out of 60 (75%) participants in post workshop answered all questions. All 15 (100%) questions were answered correctly in post workshop as compared to 11 (73.3%) questions in pre workshop. So, in post-workshop, there were significant (P <0.005) gains in knowledge regarding all good clinical practice questions. Conclusions: Good clinical practice knowledge improved markedly with a targeted education intervention in form of workshop. However, changes in behaviour and attitude were not studied by this questionnaire based study.